A rare case of traumatic gunshot wound to fetal cranium at 25 weeks gestation: A case report - Mohammed Asaad; Candace Acuff; Martina Shoukralla; Hajra Takala; Bakytbubu Arynova; Grace Chang (Trauma Case Reports)
We present a rare case of traumatic maternal gunshot wound (GSW) that resulted in fetal death due to direct fetal injury. A 21-year-old 25 week G3P1011 female with no past medical history (PMH) presented to the Emergency Department (ED) after sustaining a GSW wound to her left buttock while sitting in a car. She presented with an acute comminuted fracture of the left iliac bone, and passage of a bullet through the fetal cranium terminating near the placenta. Management consisted of immediate resuscitation, imaging, and emergent abdominal exploration leading to delivery of a non-viable fetus.